Development and characterization of core-shell nanofiber wound dressings containing Nigella Sativa and Laurus Nobilis essential oils via coaxial electrospinning - Eynur, Fatih Mehmet; Karaca, Gulcan Aysin; Kose, Alpay; Kocer, Anil tevfik; Balkanli, Didem (TAYLOR & FRANCIS LTD, 2026)
The demand for functional wound dressings for the effective management of acute and chronic wounds is increasing. The composition of functional components such as polymers and essential oils enables the development of wound dressings. In this study, a core-shell nanofiber wound dressing incorporating Nigella sativa and Laurus nobilis oils was developed using the coaxial electrospinning technique. Nigella sativa oil was incorporated into the polylactic acid outer shell, while Laurus nobilis oil was encapsulated within the polyvinyl alcohol inner core. The chemical composition of the essential oils was analyzed using Gas Chromatography-Mass Spectrometry. The fabricated nanofibers were characterized using spectroscopic and morphological analyses, contact angle measurements, mechanical testing, and biological assays. Scanning electron microscopy results revealed a homogeneous fiber morphology with average diameters of 522.8 +/- 71.9 nm. FTIR spectra indicated the presence of characteristic functional groups associated with both essential oils within the polymer matrix. Contact angle measurements (theta = 79.27 degrees) indicated moderate surface wettability, which is favorable for wound dressing applications. Tensile testing revealed an increase in mechanical strength corresponding to increased polymer layering. A high antioxidant capacity was determined using the DPPH method. Furthermore, disk diffusion assays demonstrated notable antimicrobial activity, particularly against Staphylococcus aureus (13.50 +/- 0.28 mm). MTT assays verified that the material exhibits a high level of biocompatibility and supports cell viability. In conclusion, the developed wound dressing represents a multifunctional biodegradable nanofibrous system combining antimicrobial, antioxidant, and cell- supportive properties for wound healing applications.
Keywords: Wound dressing; coaxial electrospinning; core-shell nanofibers; Nigella sativa; Laurus nobilis; FATTY OIL; ANTIBACTERIAL; FIBERS; Engineering; Materials Science; Polymer Science